2014
DOI: 10.1021/ic403040u
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Vibrational Modes in the Far-Infrared Spectra of Ruthenium Carbonyl Clusters and the Effect of Gold Substitution

Abstract: High-quality far-IR absorption spectra for a series of ligated atomically precise clusters containing Ru3, Ru4, and AuRu3 metal cores have been observed using synchrotron radiation, the latter two for the first time. The experimental spectra are compared with predicted IR spectra obtained following complete geometric optimization of the full cluster, including all ligands, using DFT. We find strong correlations between the experimental and predicted transitions for the low-frequency, low-intensity metal core v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…22 This level of theory has been utilized by us for similar ligated metal cluster systems previously, and has been shown to give good agreement to experimental results. 15,16 Except where calculating the energy of dimerization, all calculations reported are for the dimer of the Au 3 species, i.e. [{{Au(PPh 3 )} 3 (m 3 ÀO)} 2 ] 2+ (X À ) 2 , (X ¼ BF À 4 , MnO À 4 , or nothing), consistent with literature reports.…”
Section: Experimental and Computational Proceduressupporting
confidence: 84%
See 1 more Smart Citation
“…22 This level of theory has been utilized by us for similar ligated metal cluster systems previously, and has been shown to give good agreement to experimental results. 15,16 Except where calculating the energy of dimerization, all calculations reported are for the dimer of the Au 3 species, i.e. [{{Au(PPh 3 )} 3 (m 3 ÀO)} 2 ] 2+ (X À ) 2 , (X ¼ BF À 4 , MnO À 4 , or nothing), consistent with literature reports.…”
Section: Experimental and Computational Proceduressupporting
confidence: 84%
“…This region is of importance to ligated metal cluster species as vibrational modes involving metal-metal stretching appear within this region. 15,16 We have previously reported the far-infrared (50-650 cm À1 ) vibrational spectra of a range of gold, ruthenium, and gold-ruthenium species, which were accompanied by computational investigations to give an insight into the specic vibrational modes which give rise to each feature within the infrared spectra. 15,16 For all previous calculations involving species with counter-ions, the counter-ions were removed and the charge balanced for the primary cluster of interest, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that, for large main group element clusters, the B3LYP/LanL2DZ method is sufficient. [46][47][48][49][50][51] This journal is © The Royal Society of Chemistry 2015…”
Section: Computational Detailsmentioning
confidence: 99%
“…Also, the strongly size-dependent electronic properties of ultra-small metal clusters offer the opportunity to tune their reactivity by choice of appropriate size and composition. 3,4 Furthermore, such clusters are small enough to perform high level DFT calculations, 5,6,7 which are crucial for comprehensive understanding of the catalytic mechanisms needed for the development of superior catalysts. 8 Therefore, size-specific clusters are considered as a platform for investigation of catalysts at the atomic level.…”
Section: Introductionmentioning
confidence: 99%